Clinical workload in UK primary care: a retrospective analysis of 100 million consultations in England, 2007–14 - Bankhead, C; Hobbs, F; Mukhtar, T; Stevens, S; Perera, R; Holt, T; Salisbury, C (Lancet, 2016)
Background Primary care is the main provider of health care in many health systems including the NHS, but few objective data exist on activity. With rising concerns that NHS primary care workload has increased substantially, we provide the most comprehensive workload analyses yet. Methods Large retrospective analysis of routinely entered electronic health records (Clinical Practice Research Datalink) and linked datasets, based on GP and nurse consultations in 398 practices between April 2007 and March 2014. We analysed trends involving over 20 million person years of observation. Findings The crude annual consultation rate per person increased by 10.5%, from 4.67 (95% CI: 4.7 to 4.7) in 2007/8 to 5.16 (95% CI: 5.2 to 5.2) in 2013/4. Consultation rates are highest in children and the elderly, and higher for females than males at all ages. The greatest increases in age and sex standardised rates were experienced by GPs, with a rise of 12.4% over 7 years compared with 0.9% for practice nurses. GP telephone consultation rates doubled, compared to a 5.2% rise in GP surgery consultations which accounted for 90% of all GP consultations. The average duration of GP surgery consultations increased by 6.7% to 9.2 minutes and overall workload by 16% over the 7 years. These data only explore direct clinical workload and not indirect activities and professional duties which have probably also increased. Conclusions We confirm a substantial increase in practice consultation rates, average consultation duration, and total patient-facing clinical workload in English general practice over seven years to 2014. Our analyses suggest that English primary care, as currently delivered, may be reaching saturation point.